Anomalous SAXS at P12 beamline EMBL Hamburg: instrumentation and applications. (2nd May 2021) - Gruzinov, Andrey Yu.; Schroer, Martin A.; Manalastas-Cantos, Karen; Kikhney, Alexey G.; Hajizadeh, Nelly R.; Schulz, Florian; Franke, Daniel; Svergun, Dmitri I.; Blanchet, Clement E.
Abstract : Hardware and software for anomalous small‐angle X‐ray scattering on biological macromolecules in solution implemented at the P12 beamline of the EMBL (PETRA III storage ring, DESY, Hamburg) are described. Abstract : Small‐angle X‐ray scattering (SAXS) is an established method for studying nanostructured systems and in particular biological macromolecules in solution. To obtain element‐specific information about the sample, anomalous SAXS (ASAXS) exploits changes of the scattering properties of selected atoms when the energy of the incident X‐rays is close to the binding energy of their electrons. While ASAXS is widely applied to condensed matter and inorganic systems, its use for biological macromolecules is challenging because of the weak anomalous effect. Biological objects are often only available in small quantities and are prone to radiation damage, which makes biological ASAXS measurements very challenging. The BioSAXS beamline P12 operated by the European Molecular Biology Laboratory (EMBL) at the PETRA III storage ring (DESY, Hamburg) is dedicated to studies of weakly scattering objects. Here, recent developments at P12 allowing for ASAXS measurements are presented. The beamline control, data acquisition and data reduction pipeline of the beamline were adapted to conduct ASAXS experiments. Modelling tools were developed to compute ASAXS patterns from atomic models, which can be used to analyze the data and to help designing appropriate data collection strategies. These developments are illustrated with ASAXS experiments on different model systems performed at the P12 beamline.